THE RISE OF LLMS IN BUREAUCRACY AND MILITARY DECISION-MAKING AND THE CYBERSECURITY IMPERATIVE - OZDEMIR, Gloria Shkurti (Cyberpolitik Journal, 2025)
Large Language Models (LLMs) are rapidly transforming decision-making processes across bureaucratic and military institutions. Their ability to synthesize data, simulate complex scenarios, and generate real-time strategic insights is driving adoption in public sector settings, with initiatives like OpenAI’s “ChatGPT Gov” already deployed across U.S. federal agencies. However, the integration of LLMs into core governance and defense infrastructures introduces profound risks. Beyond technical concerns such as data poisoning, adversarial attacks, and insider misuse, these models also raise normative challenges, escalation bias in military applications, erosion of institutional accountability, and dependency on opaque corporate infrastructures. This article critically examines the operational use of LLMs in bureaucratic and military domains, analyzes the cybersecurity and geopolitical risks they pose, and frames their adoption within broader debates on technological sovereignty, corporate power, and data colonialism. Lastly, the article provides several recommendations that can offer some insight into how states, particularly middle and regional powers, can reclaim agency, enhance institutional resilience, and push for more effective regulatory frameworks in the face of accelerating LLM integration and corporate dominance.